Israel and the Church : the origins and effects of replacement theology - Diprose, Ronald E. (Ronald Eric); Diprose, Rinaldo (Waynesboro, GA : Authentic Media, 2004)
Traces and challenges the concept that the Church has completely and permanently replaced ethnic Israel in the outworking of God's plan throughout history by carefully reviewing relevant New Testament and post-apostolic writings.
A unique people -- Replacement theology -- The development of replacement theology in post-apostolic times -- Replacement theology and ecclesiology -- Replacement theology and eschatology -- Lessons for Christian theology -- Appendix: Israel and Christian theology : some effects of the new majority view.
Originally published: Rome : Istituto Biblico Evangelico Italiano, c2000 under the title Israel in the development of Christian thought.
Derived from parts of a dissertation for which the author was awarded the PhD in Theology by the Evangelische Theologische Faculteit, Heverlee (Louvain), Belgium, in September, 1997. The Evangelische Theologische Faculteit has given permission for this material to be published.
Includes bibliographical references (p. 237-255) and index.
Keywords: Judaism -- Relations -- Christianity; History; Church -- Biblical teaching